Application of Phage Therapy in a Case of a Chronic Hip-Prosthetic Joint Infection due to Pseudomonas aeruginosa: An Italian Real-Life Experience and In Vitro Analysis. (1st February 2023) - Cesta, Novella; Pini, Marco; Mulas, Tiziana; Materazzi, Alessandro; Ippolito, Ernesto; Wagemans, Jeroen; Kutateladze, Mzia; Fontana, Carla; Sarmati, Loredana; Tavanti, Arianna; Lavigne, Rob; Andreoni, Massimo; et al.
Abstract: Background: Prosthetic joint infection (PJI) caused by Pseudomonas aeruginosa represents a severe complication in orthopedic surgery. We report the case of a patient with chronic PJI from P. aeruginosa successfully treated with personalized phage therapy (PT) in combination with meropenem. Methods: A 62-year-old woman was affected by a chronic right hip prosthesis infection caused by P. aeruginosa since 2016 . The patient was treated with phage Pa53 (I day 10 mL q8h, then 5 mL q8h via joint drainage for 2 weeks) in association with meropenem (2gr q12h iv) after a surgical procedure. A 2-year clinical follow up was performed. An in vitro bactericidal assay of the phage alone and in combination with meropenem against a 24-hour-old biofilm of bacterial isolate was also carried out. Results: No severe adverse events were observed during PT. Two years after suspension, there were no clinical signs of infection relapse, and a marked leukocyte scan showed no pathological uptake areas. In vitro studies showed that the minimum biofilm eradicating concentration of meropenem was 8 µg/mL. No biofilm eradication was observed at 24 hours incubation with phages alone (10 8 plaque-forming units [PFU]/mL). However, the addition of meropenem at suberadicating concentration (1 µg/mL) to phages at lower titer (10 3 PFU/mL) resulted in a synergistic eradication after 24 hours of incubation. Conclusions: Personalized PT, in combination with meropenem, was found to be safe and effective in eradicating P. aeruginosa infection. These data encourage the development of personalized clinical studies aimed at evaluating the efficacy of PT as an adjunct to antibiotic therapy for chronic persistent infections. Abstract : Prosthetic joint infections caused by Pseudomonas aeruginosa are challenging infections. Phage therapy is an effective alternative antibacterial strategy. Combination of DAIR, personalized phage therapy, and meropenem was successful in the eradication of P aeruginosa from a prosthetic joint.